The Study of Plant Utilization in Aquatic Waste Management - Andri Hendrizal; Yudho Harjoyudanto (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Household, industrial, office and various other human activities produce waste. Based on the type, waste consists of liquid, solid, gas and B3. Each waste management needs to be carried out sustainable so that it will not damage the environment and human health. This paper aims to find out the effectiveness of plants in aquatic waste management. The method used in this research is literature study in the form of research articles that have been published in related fields. The data found will be analyzed descriptively qualitatively and determine the type of plant that is effective in aquatic waste management and the way plants in degrade hazardous substances that are in the waste. The results of the literature study show that some plants have a special mechanism in reducing hazardous substances contained in waste both actively and passively.